2002
DOI: 10.1103/physreve.66.046222
|View full text |Cite
|
Sign up to set email alerts
|

Chaos and flights in the atom-photon interaction in cavity QED

Abstract: We study dynamics of the atom-photon interaction in cavity quantum electrodynamics (QED), considering a cold two-level atom in a single-mode high-finesse standing-wave cavity as a nonlinearHamiltonian system with three coupled degrees of freedom: translational, internal atomic, and the field. The system proves to have different types of motion including Lévy flights and chaotic walkings of an atom in a cavity. It is shown that the translational motion, related to the atom recoils, is governed by an equation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 44 publications
1
55
0
Order By: Relevance
“…In the limit of the large argument 2/(ω r p node ), both the functions have a harmonic asymptotics [27], and the expression (18) reduces to the form…”
Section: Stochastic Map For Chaotic Atomic Transportmentioning
confidence: 99%
“…In the limit of the large argument 2/(ω r p node ), both the functions have a harmonic asymptotics [27], and the expression (18) reduces to the form…”
Section: Stochastic Map For Chaotic Atomic Transportmentioning
confidence: 99%
“…Recently cavity QED is considered in dealing with nonlinear dynamics [7,9]. Mapping quantum equations of motion onto classical ones, for the Jaynes-Cummings Hamiltonian, which includes recoil motion of the atom, Prants et al, explored phase-space dynamics of the atom interacting with a single cavity mode by analyzing Poincare surface sections and calculating Lyapunov exponents.…”
Section: Introductionmentioning
confidence: 99%
“…Mapping quantum equations of motion onto classical ones, for the Jaynes-Cummings Hamiltonian, which includes recoil motion of the atom, Prants et al, explored phase-space dynamics of the atom interacting with a single cavity mode by analyzing Poincare surface sections and calculating Lyapunov exponents. In such a case classical and not quantum chaos described by classical equations of motion corresponding to Jaynes-Cummings Hamiltonian are studied that are classical counterpart of the atom + photon + cavity system that are described by Prants et al [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…spatial) and internal (corresponding to level transitions) degrees of freedom can essentially complexify atom dynamics even in the absence of interactions between atoms. Earlier studies in the semiclassical regime for the spatial atomic dynamics revealed many intriguing phenomena like chaotic Rabi oscillations [11], chaotic atomic transport and dynamical fractals [12][13][14][15], occurrence of Lévy flights and anomalous diffusion [16][17][18], synchronization between spatial and internal dynamics [19]. A detailed theory of chaotic atomic transport of atoms in a laser standing wave has been developed in Refs.…”
Section: Introductionmentioning
confidence: 99%